(3fRhd GdZjK GdPj GfSLe aj TQM dGejI GdYLes - (3eMeO Hf CHj HcQ Hf YeQ Hf CHj HcQ Hf eMeO, GdeNRhej GdbQTj, HOQ GdOjf GdeYQha HGHf GdOeGejfj , J (B827 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gddg GdPj dG jJhLg Ydjg GdGYJQGV aEf HYV ScGf GdCScfOQjI, eef jRYe Cfg ef WdHg GdYde s
(3BNQgG (B:s
(3eY Cfj JQcJ CTjGA de CPcQgG Nha GdEWGdI hGdedd adjbJUQ Ydi gPG GdbOQ aajg caGjI, hGddg GSCd MSf GdNGJeI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3fSNI KGdKI JJab aj ChdgG hBNQgG eY GdfSNI GdChdis
(3HGNJdGa aj HYV GdCdaGXs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B57 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B115 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B180s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B152 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1938s
Keywords: (3GdCOHs